A CASE STUDY ON RISK MANAGEMENT SYSTEM OF A RURAL COOPERATIVE BANK IN INDIA - Nikam, Aditya (Indian Journal of Finance and Banking, 2024)
Rural Cooperative Banks (RCBs) are supervised by National Bank for Agriculture and Rural Development (NABARD) under CAMELSC rating framework. The CAMELSC model is principally performance-oriented while risk factors are not effectively incorporated. NABARD’s Enhanced CAMELSC model, which will be fully implemented by the end of FY26, includes additional risk and control indicators. The purpose of this study is to examine liquidity risk, interest rate risk and credit risk of a District Cooperative Central Bank (DCCB) having good financial position as per the C, A, E and L components of CAMELSC model. Name and data of the bank have been partially modified to maintain confidentiality of the data not available in public domain. The study is based on policies, committee proceedings and quantitative data obtained from a DCCB, discussion with bank officials, and periodic returns submitted to NABARD. The study employed various guidelines by RBI and NABARD. The stock and flow approaches suggested that the bank had moderate liquidity risk. Application of Interest Rate Sensitivity Statements, Macaulay Duration of investment portfolio, and MCLR methodology for interest rate benchmarking showed low interest rate risk. Altman’s z-score model illustrated credit risk in institutional clients viz. PACS and logistic regression model for retail customer scoring indicated limitation in capturing credit risk of its retail customers. The capital adequacy assessment also indicated the bank had insufficient RoA to give dividend as per its mandate. Bank did not have governance mechanism in place such as Credit Risk Management Committee or having effective ALCO to carry out executive functions of monitoring and controlling risk controls/ limits as per the policy. JEL Classification Codes: G21, G28.